Patriarchy Depiction through the Female Main Character’s Relationship in Marie Lu’s The Kingdom of Back - Wardani, Leoba Dyah Purwita; Nisrina, Nadia Meivitasari Putri; Salikin, Hairus; Basuki, Imam; Cahyawati, Erna; Murti, Ghanesya Hari (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2024)
Literary works are reflections of society’s nature in real life, and writers often emerge the issue regarding patriarchy in their literary works. Patriarchy is not a new topic and often depicted in literary works, especially in how women of patriarchy are portrayed. This study aims to determine how the practice of patriarchy is represented through the relationship between characters in The Kingdom of Back. In this qualitative research, Stuart Hall’s representation theory, particularly Michel Foucault’s discursive approach is employed to analyze the data. In addition, Sylvia Walby’s concept of patriarchy strengthens the basic assumption. The findings of this study show how The Kingdom of Back presented patriarchy that limits women's freedom and influences the relationship between the characters, which puts women to bear the damage and stand in an unequal position. The novel portrays a woman’s struggle through male domination, oppression, and exploitation in the relationship as a consequence of her desire to resist patriarchal culture, which barred her from achieving her dreams to leave a legacy through her music and composition. Nannerl finally succeeds to overcome the patriarchy barrier and struggling to live as an composer. Furthermore, as the author and diasporic subject, Marie Lu is still influenced by the deep-rooted value of patriarchy from her home country.